Anti-alzheimer and antioxidant activity of celastrus paniculatus seed - Alam, Badrul; Haque, Ekramul (© 2011 Iranian Journal of Pharmaceutical Sciences, 2016)
This article was published in Iranian Journal of Pharmaceutical Sciences [© 2011 Iranian Journal of Pharmaceutical Sciences] and the definite version is available at : http://en.journals.sid.ir/ViewPaper.aspx?ID=229292 The article website is at: http://en.journals.sid.ir/JournalList.aspx?ID=4452